Penatalaksanaan Holistik pada Anak Usia 3 Tahun dengan Skabies Melalui Pendekatan Kedokteran Keluarga di Puskesmas Tanjung Sari Natar - Ilmyasri, Siti Amalya; Putri, Sisy Rizkia; Zuraida, Reni (CV. Jasa Sukses Abadi, 2024)
Scabies is a dermatological disorder caused by the parasitic mite Sarcoptes scabei which is capable of digging tunnels in the skin and causing itching that gets worse at night. The aim of this study is to apply family doctor services based on evidence-based medicine to patients by identifying risk factors, clinical problems, and patient management based on a framework for solving patient problems using a patient centered and family approach. This study is a case report. The data obtained were primary data obtained through alloanamnesis, physical examination, and home visits and secondary data obtained from the patient's medical records. Patients and their families have poor personal hygiene. The patient's family has insufficient knowledge about scabies, the habit of using towels together, and there is no regular schedule for washing and changing bed sheets, pillowcases and blankets. After carrying out holistic and comprehensive management using a family medicine approach, patient evaluation results were obtained in the form of increased knowledge of the patient's family regarding scabies, reduced complaints, and changes in behavior in maintaining personal and environmental hygiene.